2021
DOI: 10.1021/acs.est.1c03517
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Lab-on-Chip Spectrophotometric pH Sensor for Autonomous In Situ Seawater Measurements to 6000 m Depth on Stationary and Moving Observing Platforms

Abstract: We report a new, autonomous Lab-on-Chip (LOC) microfluidic pH sensor with a 6000 m depth capability, ten times the depth capability of the state of the art autonomous spectrophotometric sensor. The pH is determined spectrophotometrically using purified meta-Cresol Purple indicator dye offering high precision (<0.001 pH unit measurement reproducibility), high frequency (every 8 min) measurements on the total proton scale from the surface to the deep ocean (to 600 bar). The sensor requires low power (3 W during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…The automated real-time observation of carbonate chemistry dynamics with sensors like LOC offer a potentially substantial improvement in that regard. While the performances of the LOC sensor for high-resolution spectrophotometric pH measurements has been demonstrated in surface waters of shelf seas with salinities above 24 (Rérolle et al, 2018;Yin et al, 2021), this is the first report on deployments of the sensor in dynamic estuarine waters (S<20).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The automated real-time observation of carbonate chemistry dynamics with sensors like LOC offer a potentially substantial improvement in that regard. While the performances of the LOC sensor for high-resolution spectrophotometric pH measurements has been demonstrated in surface waters of shelf seas with salinities above 24 (Rérolle et al, 2018;Yin et al, 2021), this is the first report on deployments of the sensor in dynamic estuarine waters (S<20).…”
Section: Discussionmentioning
confidence: 91%
“…Under oceanic conditions, spectrophotometric pH measurement systems have demonstrated excellent performance (Clayton and Byrne, 1993;Bellerby et al, 2002;Aßmann et al, 2011;Rérolle et al, 2016). Commercially available, submersible spectrophotometric sensors (see Table 1, Lab-on-Chip (LOC) and SAMI-pH) have been successfully tested for fine-scale, autonomous and in situ monitoring of pH in a wide variety of environments, from freshwater (Martz et al, 2003) to seawater (Seidel et al, 2008;Rérolle et al, 2018;Yin et al, 2021). Indicator impurities and wavelength accuracy of spectrophotometers are some of the potential sources of uncertainty in spectrophotometric pH measurements, which DeGrandpre et al (2014) has reported in detail.…”
Section: Hco Aq Co Aq H Aqmentioning
confidence: 99%
See 3 more Smart Citations